On the quick estimation of probability of recovery from COVID-19 during first wave of epidemic in India: A logistic regression approach - Hemlata Joshi; S. Azarudheen; M. S. Nagaraja; Singh Chandraketu (Statistics in Transition new series (SiTns), 2022)
The COVID-19 pandemic has recently become a threat all across the globe with the rising cases every day and many countries experiencing its outbreak. According to the WHO, the virus is capable of spreading at an exponential rate across countries, and India is now one of the worst-affected country in the world. Researchers all around the world are racing to come up with a cure or treatment for COVID-19, and this is creating extreme pressure on the policy makers and epidemiologists. However, in India the recovery rate has been far better than in other countries, and is steadily improving. Still in such a difficult situation with no effective medicine, it is essential to know if a patient with the COVID-19 is going to recover or die. To meet this end, a model has been developed in this article to estimate the probability of a recovery of a patient based on the demographic characteristics. The study used data published by the Ministry of Health and Family Welfare of India for the empirical analysis.
Keywords: 519; COVID-19; epidemic; coronavirus disease; recovery estimation; logisticregression; logit analysis